Research Methodology : A Step-by-Step Guide for Beginners - Ranjit Kumar (New Dilhi SAGE Publications India (Pvt.) Ltd., 2014)
Research Methodology: A Step-by-Step Guide for Beginners has been written specifically for students with no previous experience of research or research methodology. The book breaks the process of designing and doing a research project into eight manageable steps. The book offers practical advice on: - Formulating a research question - Ethical considerations - Carrying out a literature review - Choosing a research design - Selecting a sample - Collecting and analysing qualitative and quantitative data - Writing a research report. The book is essential reading for undergraduate and postgraduate students in the social sciences embarking on qualitative or quantitative research projects.
A Step-by-Step Guide for Beginners.
Keywords: Social sciences--Research--Methodology -- Research--Methodology -- Research